Perancangan Sistem Informasi Rekam Medis Elektronik di Laboratorium Rekam Medis Stikes Husada Borneo - Rina Gunarti; Ni Wayan Kurnia Widya Wati; Muhammad Amin (Jurnal Kesehatan Indonesia, 2021)
An electronic medical record information system is a system that provides information on patient data reports and medical records during treatment and storage of all patient data. The filing management system at the Medical Record Laboratory of Husada Borneo Institute of Health Sciences has not been computerized. The patients’ data input still uses paper, while the recording and storage of medical records are performed manually. This study aimed to create an application related to the electronic medical record information system at the laboratory of Husada Borneo Institute of Health Sciences. This descriptive study used a qualitative approach. It was conducted on the person in charge of the medical record laboratory. Based on the study results using questionnaires and observation, the data related to the recording of outpatient medical records (e.g., medical record numbers, patient data, and disease data) were required in designing an electronic medical record information system application.